2007
DOI: 10.1016/j.ccr.2007.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Human C-Reactive Protein Binds Activating Fcγ Receptors and Protects Myeloma Tumor Cells from Apoptosis

Abstract: Elevated levels of C-reactive protein (CRP) are present in many disease situations including malignancies and may contribute to the pathogenesis of cardiovascular disorders. This study was undertaken in a myeloma setting to determine whether CRP affects tumor cell growth and survival. We show that CRP enhanced myeloma cell proliferation under stressed conditions and protected myeloma cells from chemotherapy drug-induced apoptosis in vitro and in vivo. CRP binds activating Fcgamma receptors; activates PI3K/Akt,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 43 publications
2
85
0
1
Order By: Relevance
“…35 C-reactive protein (CRP) as well as albumin levels are known to be hallmarks of tumor activity. 36,37 Taking all these facts into consideration, we can anticipate that serum miRNA levels are associated with tumor mass and disease activity. Interestingly, such correlation pattern with biochemical parameters was observed also for MGUS.…”
Section: Discussionmentioning
confidence: 99%
“…35 C-reactive protein (CRP) as well as albumin levels are known to be hallmarks of tumor activity. 36,37 Taking all these facts into consideration, we can anticipate that serum miRNA levels are associated with tumor mass and disease activity. Interestingly, such correlation pattern with biochemical parameters was observed also for MGUS.…”
Section: Discussionmentioning
confidence: 99%
“…22 A recent study in myeloma demonstrated that CRP directly promoted tumor cell proliferation under stressed conditions and protected myeloma cells from chemotherapy-induced apoptosis. 23 Clearly, further preclinical studies in HCC are needed to elucidate the causal mechanisms of CRP in HCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…A myriad of agents targeting varied facets of the innate immune system, including chemokine, interleukin-6 and tumour necrosis factor antagonists, are already in clinical trial. 7 Furthermore, it is now established that CRP plays a direct role in malignant progression 57 and is itself a valid therapeutic target, 58 with several small molecule inhibitors in development. Future studies must define the interplay between the varied facets of the inflammatory response, including the role of particular leucocyte subtypes and cellular products, to enable the rational design and allocation of anti-inflammatory strategies in this context.…”
Section: Discussionmentioning
confidence: 99%